Mosaic Turner Variant Adult Female Presenting with XO/XY Karyotype - Sigin George; Vikas Karamchand Dagar; N. Nagaraja; Barun Kumar Chakrabarty (Journal of Human Reproductive Sciences)
Turner syndrome (TS) is the most frequently detected chromosomal abnormality in females caused by the partial or complete absence of second X chromosome. Due to varied phenotypical presentation, the diagnosis of TS can create a spectrum of clinical concerns related to morbidity and mortality. At least 10% of Turner females exhibit the presence of Y chromosome or Y-derived sequences. Patients with 45,X/46,XY mosaicism may have a phenotypic variation of the external genitalia and exhibit features ranging from normal male to ambiguous to female genitalia with features of TS. Turner mosaic variants with Y chromosome components have increased risk for gonadoblastoma. Although the risk is not exactly quantifiable, according to the 2016 Cincinnati International TS Meeting Clinical Practice guidelines, bilateral prophylactic gonadectomy is mandatory if Y chromosomal component is identified in mosaic Turner. We describe a rare case of an adult female patient detected as mosaic Turner variant with the presence of Y chromosome and reconfirmed by an aneuploidy FISH probe.